Exploring the Validity of a Second Language Intercultural Pragmatics Assessment Tool. Issue 1 (2nd January 2017) - Timpe-Laughlin, Veronika; Choi, Ikkyu
ABSTRACT: Pragmatics has been a key component of language competence frameworks. While the majority of second/foreign language (L2) pragmatics tests have targeted productive skills, the assessment of receptive pragmatic skills remains a developing field. This study explores validation evidence for a test of receptive L2 pragmatic ability called the American English Sociopragmatic Comprehension Test (AESCT), which is a Web-based assessment consisting of 54 tasks measuring knowledge of speech acts, routine formulae, and culture-dependent lexical differences. The AESCT is intended to be used as a learning-oriented assessment in university-level applied linguistics classes. This study collected evidence on construct validity supporting the AESCT design as a measure of pragmatic comprehension and for providing feedback in low-stakes learning contexts; 97 university-level English language learners took the AESCT along with the Cambridge Placement Test and a background questionnaire on their exposure to target language input. Descriptive statistics, correlation analyses, and linear regression were used to analyze aspects of construct validity. Results indicate that the AESCT is sufficiently reliable. Overall, learners were found to perform as previous research suggests: sociopragmatic knowledge was related to L2 exposure and L2 proficiency. Alongside future research into L2 pragmatics test validation, implications for instruction-oriented utilization of the AESCT are discussed.